A STUDY OF THE PHILOSOPHY OF EDUCATION ON JAVANESE SCRIPT ENCODED LEARNING MEDIA - Retnowati, Herni; Ahmadi, Anas (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
Abstract: This study explores the integration of educational philosophy into the design of Javanese Script Envelope media, focusing on epistemology, ontology, axiology, and dakwah in education. In an era of globalization and digitalization, preserving local culture and identity has become increasingly challenging, particularly among younger generations. This research examines how the Javanese Script Envelope media can serve as an educational tool that not only teaches language but also fosters cultural awareness, moral values, and spiritual growth. By applying epistemological principles, the media encourages active learning and critical thinking, allowing students to construct knowledge through engagement with cultural symbols. From an ontological perspective, the study highlights the significance of viewing the Javanese script as a living cultural symbol that connects students to their heritage. In terms of axiology, the media promotes values such as respect for culture, character development, and national pride. The integration of dakwah provides a moral and spiritual framework that aligns with Islamic teachings, guiding students toward personal responsibility and community engagement. This research demonstrates that educational media, when designed with philosophical foundations, can offer a holistic learning experience that connects knowledge, culture, and values.